HUMAN RESOURCES DEVELOPMENT THROUGH MSMES IN THE DIGITAL ERA TO IMPROVE THE ECONOMY LOCAL IN SURABAYA - Supriyadi, Supriyadi; Sholahuddin, Muhammad Akmal; Setianingsih, Ayu Puspita (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study discusses the implementation of Human Resource development strategies (HR) in supporting the growth of the Micro, Small, and Medium Enterprises sector (MSMEs) and their impact on the local economy. The main objective of this strategy is empowering MSMEs to be more competitive in the market and able to face challenges, including visitor limitations. Method: The approaches implemented include socialization and training, digital marketing and promotion, and collaboration and partnerships. Results: Socialization and training have proven to be effective in increasing the knowledge and skills of MSME actors, especially in digital marketing and business management. Digital marketing strategies expand market reach, while collaboration with various parties strengthens the competitiveness of MSMEs locally and internationally. Research results show that HR development strategies not only contribute to increasing local economic income but also open up employment opportunities and improve community welfare. Novelty: This strategy is proposed as a sustainable approach to strengthening the local economy through the development of innovative and independent MSMEs.